Polyploidy influences plant–environment interactions in quaking aspen (Populus tremuloides Michx.). (26th September 2017) - Greer, Burke T; Still, Christopher; Cullinan, Grace L; Brooks, J Renée; Meinzer, Frederick C
Abstract: Quaking aspen ( Populus tremuloides Michx.), a widespread and keystone tree species in North America, experienced heat and drought stress in the years 2002 and 2003 in the southwestern United States. This led to widespread aspen mortality that has altered the composition of forests, and is expected to occur again if climate change continues. Understanding interactions between aspen and its environments is essential to understanding future mortality risk in forests. Polyploidy, which is common in aspen, can modify plant structure and function and therefore plant–environment interactions, but the influence of polyploidy on aspen physiology is still not well understood. Furthermore, the ploidy types of aspen have different biogeographies, with triploids being most frequent at lower latitudes in generally warmer and drier climates, while the northerly populations are virtually 100% diploid. This suggests that ploidy–environment interactions differ, and could mean that the ploidy types have different vulnerabilities to environmental stress. In this study, to understand aspen ploidy–environment interactions, we measured 38 different traits important to carbon uptake, water loss and water-use efficiency in diploid and triploid aspen in Colorado. We found that triploid aspen had lower stand density, and greater leaf area, leaf mass, leaf mass per area, percent nitrogen content, chlorophyll content and stomatal size. These differences corresponded to greater potential net carbon assimilation ( A, measured using A / C i curves, and chlorophyll fluorescence) and stomatal conductance ( g s ) in triploids than diploids. While triploid aspen had higher intrinsic water-use efficiency (iWUE, calculated from measurements of δ 13 C in leaf tissue), they also had greater potential water loss from higher measured g s and lower stomatal sensitivity to increasing vapor pressure deficit. Therefore, despite greater iWUE, triploids may have lower resilience to climate-induced stress. We conclude that ploidy type strongly influences physiological traits and function, and mediates drought stress responses in quaking aspen.